Environmentally friendly aspects of assisted reproduction: Innovations for the future health of the planet and humanity - Dzhambekova Zalina; Baitulaeva Kheda; Astemirova Khava; Shandaulov Asylbek; Khamchiev Kureysh; Zhiengalieva Ardak (BIO Web of Conferences)
This paper explores the environmentally friendly aspects of assisted reproduction techniques and discusses innovative approaches aimed at promoting the future health of the planet and humanity. Assisted reproduction technologies have revolutionized fertility treatments, but their environmental impact has raised concerns. The paper examines sustainable practices within assisted reproduction, such as reducing energy consumption, minimizing waste generation, and adopting eco-friendly materials. It also discusses emerging innovations in the field, including advancements in cryopreservation techniques, development of biodegradable materials for medical devices, and utilization of renewable energy sources. By addressing the environmental footprint of assisted reproduction, this paper aims to contribute to the sustainability of both human health and the planet.